Estudo e modelagem do tratamento de efluente líquido utilizando microalga Chlorella vulgaris - Carvalho, Yasmin Oliveira (2019)
The tertiary treatment provided by microalgae is presented as a profitable and promising process, combining the removal of the main nutrients causing eutrophication to the production of valuable biomass. Due to the nonlinear characteristic presented by biotechnological processes, it is possible to model these processes from tools such as Experimental Design and Artificial Neural Networks, and can predict the behavior of the main variables in wastewater treatment processes. The tertiary treatment promoted by the microalgae Chlorella vulgaris showed high nutriente removals, above 70% of phosphate and 99% of ammonium ion. Based on nutrient removal, the process was modeled through two tools, Experimental Design and Artificial Neural Networks. The mathematical model provided by the Experimental Design was representative of the tertiary treatment of sanitary effluent with the C. vulgaris microalgae as a function of the test variables. The optimum performance of the artificial neural network, with R2 of test higher than 0.95 allows the use of this tool in real applications, as in the control system in wastewater treatment plants. In order to promote a sustainable treatment, natural biomass drying was performed, which presented centesimal composition of 29% of soluble carbohydrates, 11% of lipids and 8.7% of proteins. The biomass produced has high added value and can be destined for the production of biofuels or animal feed. Thus, the tertiary treatment of effluent with microalgae is a great alternative for sustainable and lowcost treatment and can be used in wastewater treatment plants. The process aims to reduce the contamination of water resources and eutrophication of the bodies, in addition to the economic and environmental impacts generated by the biomass produced.